Renewable diesel production by hydrothermal decarboxylation of fatty acids over platinum on carbon catalyst. Issue 8 (14th September 2021) - Edeh, Ifeanyichukwu; Overton, Tim; Bowra, Steve
Abstract: For over a decade researchers have been investigating the potential to produce renewable diesel from fatty acid, possibly because it possesses good qualities such as very high cetane number, oxidative stability, and renewability, and can be produced and transported using existing refinery process facilities, making it a potential substitute for petroleum diesel. Most of these investigations required the use of organic solvents and hydrogen which might increase the cost of production. To avoid this, the current work was conducted in an aqueous medium without the addition of hydrogen, using hydrothermal decarboxylation of palmitic and oleic acids in the presence of 5% platinum on carbon catalyst. The performance of the primary products pentadecane and heptadecane obtained was optimized by determining the optimum operating conditions of temperature and residence time. The results showed that the highest molar yield of pentadecane from palmitic acid was 55.3% at the optimum conditions of 290 °C and 1.5 h, and that of heptadecane from oleic acid was 16.4% at 290 °C and 4 h. With these results the cost of production might be reduced and using a benign, environmentally friendly medium would help to reduce the risk associated with the use of organic solvents.